Antimicrobial Potential of Bacteriophages JG005 and JG024 Against Pseudomonas aeruginosa Isolates from Canine Otitis - Maura R. Lourenço; Eva Cunha; Luís Tavares; Manuela Oliveira (Veterinary Sciences)
Canine otitis externa caused by Pseudomonas aeruginosa is a relevant disease in veterinary medicine. Given P. aeruginosa’s high priority status for the development of new antimicrobials, innovative strategies like bacteriophage therapy are essential. Lytic bacteriophages are viruses with high specificity for their bacterial hosts, making them a promising therapeutic choice in both human and veterinary medicine. This study aimed to evaluate the antimicrobial potential of bacteriophages JG005 and JG024, first characterized in terms of their biofilm-forming ability and antimicrobial susceptibility profile, against P. aeruginosa isolates obtained from dogs with otitis externa,. Bacteriophages titer, host range, and activity were assessed against P. aeruginosa biofilms via microtiter assays using crystal violet and Alamar Blue. JG024 showed lytic activity against 61.2% (n = 30/49) of the isolates, while JG005 showed lytic activity against 38.8% (n = 19/49) of the isolates. Crystal violet quantification showed that JG005 can promote strong microbial suppression of 60% (n = 6/10) and 50% (n = 5/10) of the isolates at a multiplicity of infection (MOI) of 10 and 100, respectively. JG024 presented strong microbial suppression of 20% (n = 2/10) of the isolates regardless of the MOI level tested. These phages show promising potential as an innovative treatment for canine otitis externa caused by P. aeruginosa, but further studies are needed before future clinical use.